Young people navigating musical lives : Considering arts participation as agency in cultural authorship - Kuoppamäki, Anna; Vilmilä, Fanny (Sage, 2023)
This study explores young people’s arts participation through music-making in Finland and the factors that may regulate that participation. It seeks to understand the construction of active modes of arts participation in and through adolescents’ musical life courses. The interview study was conducted with young people (N = 18) participating in musical activities in formal and nonformal learning spaces, such as music institutions or activities offered by municipal youth programs. By introducing five musical pathways based on young people’s life courses, we explore the ways that adolescents negotiate individual and collective meanings as creative agents in their musical lives. The study shows that access to music education, webs of support, and continuity of musical activities are the key factors regulating young people’s arts participation through cultural authorship.
Keywords: musiikkikasvatus; musiikki; nuoret; identiteetti; osallistuminen; nuorisokulttuuri; toimijuus; luovuus; kulttuuri